Proton conductivity improvement of polymer electrolyte membrane using nano-scale explosion of water in the membrane - Kim, Sun Ha; Mehmood, Asad; Ahn, Yeonho; Kim, Hyo-Sik; Ha, Heung Yong; Kim, Dukjoon; Han, Oc Hee (ELSEVIER SCIENCE SA, 2016)
Proton conductivity of polymer electrolyte membrane (PEM) is greatly governed by the amount and distribution of water as well as morphology and alignment of hydrophilic channels forming the ion cluster network in the PEM. However, The water in PEM during hot-pressing above the glass-transition temperature of PEM and the boiling point of water has not been expected to influence the proton conductivity. Here we show that higher water amount of PEMs during the hot-pressing process results in better fuel cell performance due to shortcut-proton-pathways generated by the sudden water explosion on the nano-scale. Our results demonstrate a new post-PEM-processing method to enhance proton conductivity without additional tool/procedure, and provide some clues to the behavior of liquid molecules embedded on the nano-scale in polymers. This may open a new door to nano-scale explosion of water and/or other small liquid molecules for morphological change of pores/channels in polymer. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: METHANOL FUEL-CELL; NAFION MEMBRANES; NMR; PERFORMANCE